(untitled) (Research, Society and Development, 2020)
The present study focuses on food consumption and the implications of nutritional deficiencies in students with attention deficit hyperactivity disorder, as they understand that inappropriate eating habits contribute to the worsening of the disorder symptoms. The objective was to carry out an integrative review on the influence of inadequate food consumption and nutritional deficiencies in schoolchildren with ADHD. Articles were selected in the last eight years (2012 to 2020), in Portuguese and English. The search for the articles was carried out in three online electronic databases: Scielo, Google academic and PubMed, using the following descriptors: ADHD, Food consumption, Eating behavior, Schoolchildren. From the descriptors, 30 articles were selected, and shortly after the application of the inclusion and exclusion criteria, 10 articles remained, being 9 in English and 01 in Portuguese. It was possible to observe that children with ADHD had micronutrient deficiencies compared to the control group and that there is an association between inadequate food consumption and the worsening of the characteristic symptoms of the disorder. It is concluded that a healthy diet with the inclusion of foods rich in iron, zinc, calcium, omega-3 polyunsaturated fatty acids, vitamins B-2, B6, B-12, K and E, may reduce the characteristic symptoms of ADHD, improving the quality of life and on the other hand, unhealthy, processed, industrialized foods can aggravate the symptoms of ADHD and reflect negatively mainly in the increase of the levels of hyperactivity.